KERJASAMA KEMITRAAN, PELATIHAN APLIKASI TEKNOLOGI INFORMASI DAN KOMUNIKASI - Paryanti, Ninik; -, Sugeng; Irwan, Dadan; Samsiana, Seta; Nugroho, Retno; Gunarti, Anita S S; Rokhman, Taufiqur; Paronda, Abdul Hafid (LPPM Universitas Islam 45 Bekasi, 2020)
One of the developments to improve the economy is technology. The development of information technology, especially in the computer sector, has experienced rapid development. Information and communication technology has developed in all fields. One of the efforts to implement in terms of computer expertise requires training and development. One of the most effective things that can be used to develop society is through providing training. The results of the Information and Communication Technology Application training program to improve the quality of skills for residents of Srikamulyan Village, Tirtajaya District, Karawang Regency are in accordance with the objectives of the cooperation (MoU) agreed by both parties. This training went smoothly and all the participants attended and were very enthusiastic about following the material taught in the training